Pemberian Mulsa Terhadap Tujuh Varietas Kacang Hijau dan Keharaan Tanah di Lahan Lebak Tengahan - Yulia Raihana; Eddy William (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2006)
The objectives of this research were to obtain several mungbean varieties which suitable under fresh water swamp land conditions and to study the effect of mulch application on mungbean and soil nutrient in fresh water swamp land area. The research was conducted on water swamp land of Tawar village, Hulu Sungai Selatan in dry season of 2004. The results showed that the yield and the yield components of mungbean were not affected by mulch application. On the other hand, there were yield differences among mungbean varieties. Mulch application significantly decreased soil-pH, soil organic-C, total-P, available-P and K uptake but increased soil total-N and P uptake. Key words : Mulch, mungbean, swamp land